2016
DOI: 10.1111/jgs.14015
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve, Incident Dementia, and Associated Mortality in the Ibadan Study of Ageing

Abstract: The findings confirm the low incidence of dementia in this population, as previously reported. The condition is nevertheless associated with higher risk of mortality. Along with some features of social disadvantage, proxies of lower cognitive reserve were risk factors for incident dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 18 publications
(26 reference statements)
1
24
2
1
Order By: Relevance
“…Mortality estimates from other cohort studies in LMIC vary greatly in comparison to each other and to those of high-income countries. For example, the mortality rate per 1000 person-years in people with dementia aged ≥65 in the Ibadan Study of Ageing in Nigeria [34] was 83.1, which was similar to the estimates we found in Venezuela, Mexico, and Peru. A Chinese study conducted in Beijing found a higher crude mortality rate of 236 per 1000 person-years among people with dementia [35].…”
Section: Discussionsupporting
confidence: 88%
“…Mortality estimates from other cohort studies in LMIC vary greatly in comparison to each other and to those of high-income countries. For example, the mortality rate per 1000 person-years in people with dementia aged ≥65 in the Ibadan Study of Ageing in Nigeria [34] was 83.1, which was similar to the estimates we found in Venezuela, Mexico, and Peru. A Chinese study conducted in Beijing found a higher crude mortality rate of 236 per 1000 person-years among people with dementia [35].…”
Section: Discussionsupporting
confidence: 88%
“…[31][32][33]. Higher impairment of cognitive function may reduce the survival rate because of the beginning processes of the pathophysiology of dementia [32,34,35]. It is very important to mention the possible pathway through vascular cognitive impairment, where the role of micro-infarcts, micro-hemorrhages, strategic white matter tracts, loss of microstructural tissue integrity, and secondary neurodegeneration becomes crucial [17].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive decline occurs along a continuum [ 1 , 2 ], spanning what has been described as ‘normal ageing’, to the other end of the spectrum of cognitive impairment and dementia. Studies have shown increased risk of mortality with dementia [ 3 5 ] and cognitive impairment [ 6 8 ]. However, in an ageing population, understanding the nature of this relationship across the continuum may provide insight into the different trajectories of decline.…”
Section: Introductionmentioning
confidence: 99%